2005
DOI: 10.1097/01.prs.0000172763.71043.b8
|View full text |Cite
|
Sign up to set email alerts
|

Speech, Cognitive, and Behavioral Outcomes in Nonsyndromic Craniosynostosis

Abstract: Nonsyndromic craniosynostosis is often associated with cognitive, speech, and/or behavioral abnormalities. The etiopathology of this association is unknown. Furthermore, the proportion of children diagnosed with cognitive and behavioral dysfunction increases with age. Therefore, longitudinal cognitive, behavioral, and speech assessment and treatment are integral to the care of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 13 publications
5
120
2
2
Order By: Relevance
“…Follow-up from surgery in the present study was 111.0 months (range 40.9 to 164.8 months), with an average patient age at survey completion of 10.2 years, which is longer than the follow-up of several other studies investigating this topic (2,3,5,6,19). Additionally, unlike other studies, all of the patients in the present study underwent surgical intervention for their SSC (2,10,19,20). It should be noted, however, that some authors contend that mental development in SSC may not be affected by surgical correction (2,9,(20)(21)(22)(23).…”
Section: Discussioncontrasting
confidence: 43%
“…Follow-up from surgery in the present study was 111.0 months (range 40.9 to 164.8 months), with an average patient age at survey completion of 10.2 years, which is longer than the follow-up of several other studies investigating this topic (2,3,5,6,19). Additionally, unlike other studies, all of the patients in the present study underwent surgical intervention for their SSC (2,10,19,20). It should be noted, however, that some authors contend that mental development in SSC may not be affected by surgical correction (2,9,(20)(21)(22)(23).…”
Section: Discussioncontrasting
confidence: 43%
“…This rate is consistent with findings of several studies that examined developmental attainment, learning disability, and speech and language abnormalities in isolated SC. 7,8,13,14,33,44,46 Although, in 1982, Renier et al 41 found that raised ICP was correlated with lower IQ, more recent studies 6,23,34 have failed to confirm the relationship between elevated ICP and neurocognitive outcomes in SC or other single-suture craniosynostosis. The lack of a correlation between developmental delay and raised ICP found in the present study supports the hypothesis that there is no simple causal relationship between ICP and neurocognitive anomalies found in SC.…”
mentioning
confidence: 97%
“…Shipster et al 32 observaron funcionamiento cognoscitivo normal, mientras que otros reportan alteraciones en el lenguaje [32][33][34][35][36] , en la cognición 33,36 , en la motricidad 36 y en la conducta 33 . El hallazgo más frecuente es el déficit en el lenguaje, los distintos estudios mencionan porcentajes variables de pacientes con estas alteraciones, desde el 30% 33,35 hasta el 50% 32,34 . También se menciona que los pacientes con craneosinostosis simple tienen de 1,5 a 2 veces mayor probabilidad de presentar alteraciones cognitivas, de lenguaje y motoras que en la población normal 36 .…”
Section: Etapa Preescolarunclassified
“…La mayoría de los estudios que mencionan el funcionamiento cognoscitivo en esta edad no tienen grupo control [32][33][34][35] y algunos las muestras son pequeñas para establecer una relación causal entre las alteraciones encontradas y la craneosinostosis 34,35 , además el estudio de Mendonca 35 no establece el instrumento que utilizó para evaluar el lenguaje. …”
Section: Etapa Preescolarunclassified